Is Religion a Barrier to Peace? Religious Influence on Violent Intrastate Conflict Termination - Deitch, Mora (Terrorism and political violence, 2022)
In recent years, a burgeoning literature has emerged on the relationship between religion and conflict. Contradictory theories address the dynamics and termination of religious violent conflicts. Some studies focus on the destructive role of religion, arguing that religious conflicts are longer, more violent, and intractable. Others argue that religion has an ambivalent role, both destructive and constructive, and recognize religion as a force for peacebuilding. This study focuses on the relationship between religion and conflict termination by examining termination outcomes, based on the length and the level of violence, as well as incidents of reoccurrence. The study quantitatively examines 118 domestic conflicts between 1990 and 2014, utilizing the Political Instability Task Force and Religion and State datasets. The findings suggest that religious conflicts are likely to last longer than non-religious ones. However, the study reveals that religion has no strong significant influence on conflict termination as well as on the reoccurrence of conflicts and the violence level.